An Oxygen‐Insensitive Hydrogen Evolution Catalyst Coated by a Molybdenum‐Based Layer for Overall Water Splitting. (13th April 2017) - Garcia‐Esparza, Angel T.; Shinagawa, Tatsuya; Ould‐Chikh, Samy; Qureshi, Muhammad; Peng, Xuyuan; Wei, Nini; Anjum, Dalaver H.; Clo, Alain; Weng, Tsu‐Chien; Nordlund, Dennis; Sokaras, Dimosthenis; Kubota, Jun; et al.
Abstract: For overall water‐splitting systems, it is essential to establish O2 ‐insensitive cathodes that allow cogeneration of H2 and O2 . An acid‐tolerant electrocatalyst is described, which employs a Mo‐coating on a metal surface to achieve selective H2 evolution in the presence of O2 . In operando X‐ray absorption spectroscopy identified reduced Pt covered with an amorphous molybdenum oxyhydroxide hydrate with a local structural order composed of polyanionic trimeric units of molybdenum(IV). The Mo layer likely hinders O2 gas permeation, impeding contact with active Pt. Photocatalytic overall water splitting proceeded using MoO x /Pt/SrTiO3 with inhibited water formation from H2 and O2, which is the prevailing back reaction on the bare Pt/SrTiO3 photocatalyst. The Mo coating was stable in acidic media for multiple hours of overall water splitting by membraneless electrolysis and photocatalysis.